A bright, red-emitting water-soluble BODIPY fluorophore as an alternative to the commercial Mito Tracker Red for high-resolution mitochondrial imaging. Issue 41 (29th September 2021) - Wang, Jiang-Lin; Zhang, Lu; Gao, Lian-Xun; Chen, Ji-Lei; Zhou, Te; Liu, Yi; Jiang, Feng-Lei
Abstract : A fully water-soluble, bright, and red fluorescent BODIPY fluorophore can achieve high-resolution mitochondrial imaging with high biocompatibility, photostability and chemical stability. Abstract : With the emergence and rapid development of super-resolution fluorescence microscopy, monitoring of mitochondrial morphological changes has aroused great interest for exploring the role of mitochondria in the process of cell metabolism. However, in the absence of water-soluble, photostable and low-toxicity fluorescent dyes, ultra-high-resolution mitochondrial imaging is still challenging. Herein, we designed two fluorescent BODIPY dyes, namely Mito-BDP 630 and Mito-BDP 760, for mitochondrial imaging. The results proved that Mito-BDP 760 underwent aggregation-caused quenching (ACQ) in the aqueous matrix owing to its hydrophobicity and was inaccessible to the cells, which restricted its applications in mitochondrial imaging. In stark contrast, water-soluble Mito-BDP 630 readily penetrated cellular and mitochondrial membranes for mitochondrial imaging with high dye densities under wash-free conditions as driven by membrane potential. As a comparison, Mito Tracker Red presented high photobleaching (the fluorescence intensity dropped by nearly 50%) and high phototoxicity after irradiation by a laser for 30 min. However, Mito-BDP 630 possessed excellent biocompatibility, photostability and chemical stability. Furthermore, clear and bright mitochondria distribution in living HeLa cells after incubation with Mito-BDP 630 could be observed by CLSM. Convincingly, the morphology and cristae of mitochondria could be visualized using an ultra-high-resolution microscope. In short, Mito-BDP 630 provided a powerful and convenient tool for monitoring mitochondrial morphologies in living cells. Given the facile synthesis, photobleaching resistance and low phototoxicity of Mito-BDP 630, it is an alternative to the commercial Mito Tracker Red.